(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This is the first paper to examine the impact of the strength of intellectual property rights protection (IPRP) in regional trade agreements (RTAs) on trade of digital services. It includes estimations of a structural gravity model for a panel of 76 countries over the period 2003–2020. The study finds that stronger IPRP in RTAs increases the digital services export among member countries. The stronger the information mobility between the trading parties, and the narrower the gap in their domestic IPRP, the more pronounced is the effect of IPRP in RTAs on promoting the trade of digital services. It provides evidence for the impact of IPRP in RTAs on the digital services trade and contributes to a deeper understanding of IPRP clauses in RTAs from the perspective of their effects on digital services trade.